Developing Mushroom MSMEs (Micro, Small, and Medium enterprises) in Mangirejo Hamlet to Facilitate Community Empowerment in Maintaining Economic Stability - Ihtiari Prastyaningrum; Hardiyanto, Denny; Mustikarini, Indriyana Dwi (Jurnal Inovasi Sains dan Teknologi untuk Masyarakat, 2024)
Small and medium-sized micro enterprises (UMKM) are one of the economic activities that can improve the economy of the community. The empowerment of UMKM as an attempt to improve the economy of the post-Covid 19 pandemic community was also carried out by the citizens of Dusun Mangirejo district of Saradan, Madiun district. The initial purpose of cultivating this mushroom was to create positive activities for mothers around the UMKM site. In addition, this activity is also expected to increase the input of the UMKM. The strategy used by UMKM managers is that they have not used labelling, product packaging and have not mastered design. The solution to be achieved is to use technology as a means of marketing, in addition to the labelling and peckaging of products to expand the product distribution market. Activities in the implementation of dedication include socialization of product labeling, product packaging design skills training, and socialisation of product marketing with media sosial. Results of activities show that socialization and training activities have a significant impact on UMKM Sido Lancar. This is evident in the ability of UMKM perpetrators to design simple logos, design product packaging labels, as well as their ability to promote through media sosial.